Challenges in Growth of Livestock and Dairy Development Sector In Punjab: Potential and Innovative Solutions: a Review - Rehman, Munib ur; Mumtaz, Ammara (Devotion : Journal of Research and Community Service, 2023)
Livestock and dairy farming make up the bulk of Pakistan’s economy. Punjab is the hub of agriculture and livestock due to its land and climatic features. However, there have been a lot of challenges that are slowing down the progress. Pandemics, epidemics and climate catastrophes have caused the major impact. Dairy farming is providing livelihood to rural communities but some environmental hazards are also associated with it like greenhouse gases, deforestation etc, animal welfare as well. Sustainable livestock and dairy farming practices are widely applied worldwide and needed to prosper in Pakistan as well. This study is aimed at comparative review of the researches and latest techniques being tested and implemented economically and how can we adopt appropriate techniques to improve the current situation of this sector. There are many latest techniques that offer environmentally friendly livestock and enhanced production to serve the economy and conserve the biodiversity like precison livestock farming, smart farming, real time monitoring using biosensors for eary diagnoses and prognosis of diseases, detection of feeding patterns, breeding patterns etc. The study shows that most farmers in the study have a higher level of education, which is a positive sign for the future of the industry. The study also suggests that regular trainings be organized for farmers to transfer the latest technology and practices in a timely manner.